Pengaruh Model Pembelajaran Contextual Teaching and Learning Berbasis Tri-N terhadap Hasil Belajar IPS - Kristina Lestiyarini; Heri Maria Zulfiati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Elementary Social Studies (IPS) learning still faces challenges, particularly low student engagement and the absence of instructional models that effectively connect concepts to real-life experiences. This situation highlights the need for a more contextual and meaningful learning approach. The Tri-N–based contextual learning model—emphasizing niteni (observing), niroke (imitating), and nambahi (modifying)—is considered to have strong potential to enhance learning interaction; however, its application in elementary Social Studies remains underexplored, creating a research gap in the development of holistic instructional models. This study aims to examine the effectiveness of the Tri-N–based contextual learning model in improving Social Studies learning outcomes among elementary school students. A quantitative experimental method with a one-group pretest–posttest design was employed, involving 27 fourth-grade students. Learning outcomes were measured using a validated achievement test, and data were analyzed using a paired t-test to determine significant differences between pretest and posttest scores. The results show an increase in the average score from 61.81 to 85.03 after the implementation of the model, indicating a statistically significant improvement. These findings confirm that the Tri-N–based contextual learning model is effective in enhancing Social Studies learning outcomes and contributes to strengthening contextual instructional practices that integrate niteni, niroke, and nambahi.